2023
DOI: 10.3847/1538-4357/acb8b0
|View full text |Cite
|
Sign up to set email alerts
|

The Mass Fallback Rate of the Debris in Relativistic Stellar Tidal Disruption Events

Abstract: Highly energetic stellar tidal disruption events (TDEs) provide a way to study black hole characteristics and their environment. We simulate TDEs with the Phantom code in a general relativistic and Newtonian description of a supermassive black hole’s gravity. Stars, which are placed in parabolic orbits with different β parameters, are constructed with the stellar evolution code MESA and therefore have realistic stellar density profiles. We study the mass fallback rate of the debris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…Goicovic et al (2019) and Golightly et al (2019) found that the disruption of a 1 M e star at zero-age main sequence (ZAMS; evolved with the stellar evolution code MESA; Paxton et al 2011) yielded a peak fallback time of ∼25 days, as compared to the frozen-in prediction of ∼1 yr (see Figure 5 in Goicovic et al 2019 and Figure 2 in Golightly et al 2019). Similar results have been found by, for example, Law-Smith et al (2019, Ryu et al (2020a), andJankovič &Gomboc (2023), and some aspects of this problem have been reviewed by Wevers & Ryu (2023). Coughlin & Nixon (2022a) suggested that the discrepancy is at least partially related to the definition of the tidal radius, and in particular they noted that a star should be completely destroyed when the tidal field of the black hole exceeds the maximum self-gravitational field within the star.…”
Section: Introductionsupporting
confidence: 68%
“…Goicovic et al (2019) and Golightly et al (2019) found that the disruption of a 1 M e star at zero-age main sequence (ZAMS; evolved with the stellar evolution code MESA; Paxton et al 2011) yielded a peak fallback time of ∼25 days, as compared to the frozen-in prediction of ∼1 yr (see Figure 5 in Goicovic et al 2019 and Figure 2 in Golightly et al 2019). Similar results have been found by, for example, Law-Smith et al (2019, Ryu et al (2020a), andJankovič &Gomboc (2023), and some aspects of this problem have been reviewed by Wevers & Ryu (2023). Coughlin & Nixon (2022a) suggested that the discrepancy is at least partially related to the definition of the tidal radius, and in particular they noted that a star should be completely destroyed when the tidal field of the black hole exceeds the maximum self-gravitational field within the star.…”
Section: Introductionsupporting
confidence: 68%